EFFECTIVENESS OF PREOPERATIVE CARBOHYDRATE LOADING WITH LENGTH OF HOSPITALIZATION IN NON-INVASIVE GYNECOLOGICAL SURGERY PATIENTS: AN EVIDENCE-BASED CASE REPORT - Nita Nurul Rachman; Wina Sinaga (Perhimpunan Dokter Gizi Klinik Indonesia, 2022)
Background Carbohydrate loading is one of the steps in the preoperative procedure of Enhanced Recovery after Surgery (ERAS). The advantages of the ERAS pathway have positive effects on postoperative outcomes, including a reduction in the length of stay/LOS in hospital. Objective: This study aims to critically analyze the effectiveness of carbohydrate loading on the reduction in the length of hospital stay among patients undergoing non-invasive gynecologic surgical procedure. Methods: A search was conducted to find several literatures from PubMed, Cochrane and Scopus. This study assesses the relevance and feasibility of the literatures. The search found three selected literatures to further conduct a critical assessment. Results: A critical review was conducted towards three randomized controlled trial literatures. Two literatures showed a significant reduction in the length of stay with preoperative carbohydrate loading (p<0.001), while one literature showed an insignificant finding (p=0.684). Conclusions: Carbohydrate loading as a part of the preoperative management of ERAS could reduce the length of hospital stay among patients undergoing non-invasive gynecologic surgery procedure. Differences in the results of several studies indicate the need for further studies using the similar intervention method. Keywords: enhanced recovery after surgery, gynecologic surgery, carbohydrate loading, length of stay.